DISTRIBUTION OF ATOMICSIZED STEPS IN [100] SURFACES OF NACL MONOCRYSTALS - YACAMAN, MJ; VILLASENOR, GT (UNAM, Instit de Fisic, centro de Inves Materiales, 1969)
Abstract only given, as follows: A knowledge of the distribution of the monatomic steps in crystalline surfaces subjected to various external conditions is of great importance in explaining surface phenomena. Using the surface decoration method, the autho
THE AUK
Keywords: DISTRIBUTION, ATOMIC, SIZED STEPS, SURFACES, NACL MONOCRYSTALS; FISICA; QUIMICA NUCLEAR; ATOMOS